1983
DOI: 10.2307/1590374
|View full text |Cite|
|
Sign up to set email alerts
|

Epizootiology of Avian Influenza: Simultaneous Monitoring of Sentinel Ducks and Turkeys in Minnesota

Abstract: Isolation-reared mallards (Anas platyrhynchos) were placed on ponds in turkey-rearing areas in Minnesota, and their cloacae were periodically swabbed to attempt isolating virus from embryonated chicken eggs. Nearby turkeys were sampled by taking cloacal and tracheal swabs as well as blood samples. Hemagglutinating viruses were identified at the National Veterinary Services Laboratory, U.S. Department of Agriculture, Ames, Iowa. During this two-year study, the weekly influenza virus-isolation rate from ducks va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(104 citation statements)
references
References 9 publications
6
96
0
1
Order By: Relevance
“…Only 5% of the 210 water samples tested in this study were positive by RT-qRT-PCR for the Influenza A matrix gene. Similar studies have documented higher detection rates in water samples, though reported prevalence varies widely by study, and in some cases with higher detection rates the water samples were collected near trapped sentinel birds or domestic ducks [4345,49]. The prevalence of influenza positive fecal samples in this study is similar to other studies of environmentally collected fecal samples in North America [20,48,50].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Only 5% of the 210 water samples tested in this study were positive by RT-qRT-PCR for the Influenza A matrix gene. Similar studies have documented higher detection rates in water samples, though reported prevalence varies widely by study, and in some cases with higher detection rates the water samples were collected near trapped sentinel birds or domestic ducks [4345,49]. The prevalence of influenza positive fecal samples in this study is similar to other studies of environmentally collected fecal samples in North America [20,48,50].…”
Section: Discussionsupporting
confidence: 84%
“…Since then, other researchers have attempted to isolate or detect avian influenza viruses in environmental samples for the purposes of surveillance. In North America, Influenza A has been detected in water samples collected in Minnesota, Alaska, Oklahoma, and California [20,4548]. Only 5% of the 210 water samples tested in this study were positive by RT-qRT-PCR for the Influenza A matrix gene.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In tests conducted in the U.S. in 1980-81, when mallards that had tested negative were put together with turkeys, virus (H4N8, H4N2, H5N2) was isolated from the mallards before or at the same time that avian influenza of the same type viruses was detected in the turkeys. However, there were also cases in which, though detected in the turkeys, the virus was not detected in the mallards (Halvorson et al, 1983). In Cambodia, H5N1 virus was first detected at the Wildlife Rescue Center (combined with the zoo) in the suburbs of Phnom Penh in December 2003.…”
Section: Wild Bird Virus Tests Following Avian Influenza Infection Inmentioning
confidence: 99%
“…The virus was initially typed as a low pathogenic avian influenza (LPAI) H6N2 strain at the VLA Weybridge laboratory, UK. In South Africa, testing of archival material from the same region traced the infection back to June 2001, but the exact source of the H6N2 outbreak was never determined.Most outbreaks ofAI in domestic poultry are thought to have originated by the transfer of viruses from feral birds [1,2]. Chickens are generally not considered to be natural hosts for AI viruses and H6 viruses have never been associated with serious disease in poultry.…”
Section: Introductionmentioning
confidence: 99%